Time in the city: long-term urban exposure predicts greater exploration and problem solving in wild red foxes - F. Blake Morton; Dylan Thompson-Jones; Kristy A. Adaway; Koko M. Sutter; Catia Matos; Georgia B. Freer; Georgia A.A. Fletcher; Carl D. Soulsbury (Animal Behaviour, 2026)

The genus Pouteria: a review of advances in phytochemical elucidation and its pharmacological properties - Rafael C. Matos; Ana Flavia A. Bitencourt; Vanessa R. Prado; Alexsandro D. M. Oliveira; Renes R. Machado; Marina Scopel (Phytochemistry Reviews, 2026)
The genus Pouteria (family Sapotaceae) is traditionally used for gastrointestinal, inflammatory, and microbial issues, and has great nutritional applications because of the variety of fruits it contains. Despite its versatile applications, comprehensive research on Pouteria remains outdated, necessitating an integrative review of recent studies exploring its phytochemical evidence and biological activities. An unrestricted search in various databases (Jan/2009 to Aug/2022) focused on the genus “ Pouteria ”. Despite this genus having 325 recognized species, few studies have evaluated their bioactive potential, including antioxidant, anticancer, hypoglycemic, antimicrobial, anti-inflammatory, and antinociceptive, as well as their potential for treatment of Alzheimer disease. Regarding phytochemical evaluation, among the few substances isolated were a high number of terpenoids, flavonoids, phenolics, saponins, and others. In addition, owing to the high potential for fruit utilization, several primary metabolites were identified, which presented qualitative and quantitative diversity among species with the interests of the pharmaceutical industry. Therefore, this review provides information about phytochemical and pharmacological properties of the species of Pouteria . Given the shallow and incomplete results for several species, there is a demonstrated need for new studies encompassing all plant parts of Pouteria species, contributing to a more comprehensive understanding of their medicinal potential.

Native Trichoderma spp. as biocontrol agents against common beans anthracnose - S. C. Izidoro-Morimitsu; A. Knob; C. K. Matos; C. M. D. R. Faria; J. Kawakami (Journal of Plant Diseases and Protection, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

The goat Longissimus thoracis et lumborum muscle proteome: effects of dry ageing and cooking in chevon - Menalda Valeriano André; Catarina Prista; Vítor D. Alves; David M. Ribeiro; Miguel Filipe Pedro; Laura Sacarrão-Birrento; Hugo Osório; André M. de Almeida; Teresa J.S. Matos (Food Research International, 2025)

Here, There and Everywhere: Widespread Non‐Native Plants in the World's Urban Ecosystems - David M. Richardson; Lauren B. Trotta; Myla F. J. Aronson; Benjamin Baiser; Marc W. Cadotte; Marta Carboni; Laura Celesti‐Grapow; Sonja Knapp; Ingolf Kühn; Ana Carolina Lacerda de Matos; Zdeňka Lososová; Daijiang Li; et al. (Global Ecology and Biogeography, 2025)
Aim To (a) produce a list of the most widespread naturalised non‐native plant species across cities of the world; (b) explore whether cities on different continents are invaded by the same group of widespread naturalised species; and (c) elucidate the origins of the most widespread naturalised urban species. Location Global. Time Period No specific period. Major Taxa Studied Vascular plants. Method Using the most comprehensive and up‐to‐date dataset of non‐native urban floras yet assembled (GUBIC; Global Urban Biological Invasions Compendium), we identified the most widespread naturalised plant species (the global urban florome) by filtering for taxa present across all continents (except Antarctica) and their frequency in urban areas. To assess global patterns of urban plant naturalisation, we conducted ordination analyses and visualised species co‐occurrence. We also examined species origins and their environmental impact. Results Among the 7792 naturalised plant species recorded in 553 urban centres, 302 species (4%) were found on all six continents. Of these, 96 species, considered the most widespread species, were present in more than half of urban centres in Oceania, North America and South America; this proportion was higher than in Africa, Asia and Europe. Cities outside Europe and Asia are more homogeneous in terms of the species composition of the most widespread invaders. An analysis of species origins showed that temperate Asia contributed the most species globally, while intercontinental exchange patterns varied, with a notable one‐directional flow from North to South America. Main Conclusions Our results suggest that urban ecosystems outside Europe and Asia are more susceptible to recent invasions than those within these two continents. Understanding the composition and origins of these widespread species is crucial for developing coordinated management strategies and improving the resilience of urban biodiversity.

Enhancing commercial SOFCs fed directly with ethanol through a modified manganite coating - F. Matos de Oliveira; S. Vecino-Mantilla; Z. Hafsi; M.V. Barp; F. D’Acapito; A. Puri; J. Perez; E. Ticianelli; M. Lo Faro (Chemical Engineering Journal, 2025)

Corrigendum to “Synthesis of controlled size starch nanoparticles (SNPs) title of article” [Carbohydr. Polym. 250 (2020) 116938] - G. Gutiérrez; D. Morán; A. Marefati; J. Purhagen; M. Rayner; M. Matos (Carbohydrate Polymers, 2025)

Insights into the thermal stability properties of two hardwoods from the Amazon rainforest - L. de Souza-Cavalcante; F. Guerrero; J. Anglada-Rivera; Y. Leyet; F. M. A. da Silva; G. Q. Ramos; R. Matos; H. D. da Fonseca Filho (Journal of the Indian Academy of Wood Science, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Metabolic response of Zostera noltei transplants in a historically contaminated ecosystem - V.H. Oliveira; D. Matos; A.I. Sousa; M. Dolbeth; B. Marques; A.I. Lillebø; M.E. Pereira; S. Díez; E. Figueira; J.P. Coelho (Journal of Environmental Management, 2025)

Transplantation of seagrass (Zostera noltei) as a potential nature-based solution for the restoration of historically contaminated mudflats - Vítor H. Oliveira; B.A. Fonte; A.I. Sousa; D. Crespo; J.M. Dias; N. Vaz; D. Matos; E. Figueira; M.E. Pereira; A.I. Lillebø; M. Dolbeth; J.P. Coelho (Science of The Total Environment, 2025)

Investigating multiple vegetable oils and recycled variant for microplastics extraction from water, integrated with Raman spectroscopy - R. Garzón-Vidueira; D. Rede; R. Rial-Otero; R. Vilarinho; J.A. Moreira; S. Jorge; M. André; R. Barbosa; C. Delerue-Matos; V. Cruz Fernandes (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Disseminated paracoccidioidomycosis in a captive western black-handed tamarin (Saguinus niger) - Isabelle D. de Oliveira; Eduardo Ferreira-Machado; Jamile M. Garcia; Sarah R.J.S. Simões; Ketlyn B. Figueiredo; Rodrigo A. Ressio; André L.M. da Costa; Flora N. Matos; Cássia R.R. Gonzaga; Shamira S. Leandro; Marina A. de Medeiros; Rodrigo H.F. Teixeira; et al. (Journal of Comparative Pathology, 2024)

SARS-CoV2 Nsp1 is a metal-dependent DNA and RNA endonuclease - Bruno A. Salgueiro; Margarida Saramago; Mark D. Tully; Federico Issoglio; Sara T. N. Silva; Ana C. F. Paiva; Cecília M. Arraiano; Pedro M. Matias; Rute G. Matos; Elin Moe; Célia V. Romão (BioMetals, 2024)
Over recent years, we have been living under a pandemic, caused by the rapid spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). One of the major virulence factors of Coronaviruses is the Non-structural protein 1 (Nsp1), known to suppress the host cells protein translation machinery, allowing the virus to produce its own proteins, propagate and invade new cells. To unveil the molecular mechanisms of SARS-CoV2 Nsp1, we have addressed its biochemical and biophysical properties in the presence of calcium, magnesium and manganese. Our findings indicate that the protein in solution is a monomer and binds to both manganese and calcium, with high affinity. Surprisingly, our results show that SARS-CoV2 Nsp1 alone displays metal-dependent endonucleolytic activity towards both RNA and DNA, regardless of the presence of host ribosome. These results show Nsp1 as new nuclease within the coronavirus family. Furthermore, the Nsp1 double variant R124A/K125A presents no nuclease activity for RNA, although it retains activity for DNA, suggesting distinct binding sites for DNA and RNA. Thus, we present for the first time, evidence that the activities of Nsp1 are modulated by the presence of different metals, which are proposed to play an important role during viral infection. This research contributes significantly to our understanding of the mechanisms of action of Coronaviruses.

The decline and death of Canary Island date palms in México City is associated with subgroup 16SrIV-D phytoplasmas - C. F. Ortiz-García; D. Alvarado-Rosales; C. Oropeza; L. de L. Saavedra-Romero; S. Aranda-Ocampo; A. Almaraz-Sánchez; A. Quezada-Salinas; A. Equihua-Martínez; S. E. García-Díaz; M. Narváez; G. Nic-Matos; P. J. Palma-Cancino; et al. (Australasian Plant Pathology, 2024)

Evaluation of chelating and cytoprotective activity of vanillin against the toxic action of mercuric chloride as an alternative for phytoremediation - Joelma P. da Silva; Maria do S. Costa; Fabia F. Campina; Camila F. Bezerra; Thiago S. de Freitas; Amanda K. Sousa; Celestina E. Sobral Souza; Yedda M. L. S. de Matos; Francisco N. Pereira-Junior; Irwim R. A. Menezes; Henrique D. M. Coutinho; Janaína E. Rocha (Environmental Geochemistry and Health, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Purinergic system as a potential target for inflammation and toxicity induced by thymol in immune cells and tissues - Matheus D. Baldissera; Carine F. Souza; Antônio Francisco Igor M. De Matos; Bernardo Baldisserotto; Lenita M. Stefani; Aleksandro S. da Silva (Molecular and Cellular Biochemistry, 2019)

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

In Silico, In Vitro and In Vivo Toxicological Assessment of BPP-BrachyNH2, A Vasoactive Proline-Rich Oligopeptide from Brachycephalus ephippium - Daniel D. R. Arcanjo; Ana Carolina Mafud; Andreanne G. Vasconcelos; José Couras da Silva-Filho; Maurício P. M. Amaral; Lucas M. Brito; Marcelo P. Bemquerer; Selma A. S. Kückelhaus; Alexandra Plácido; Cristina Delerue-Matos; Nuno Vale; Yvonne P. Mascarenhas; et al. (International Journal of Peptide Research and Therapeutics, 2017)

Evaluation of Primary Production in the Lower Amazon River Based on a Dissolved Oxygen Stable Isotopic Mass Balance - William C. Gagne-Maynard; Nicholas D. Ward; Richard G. Keil; Henrique O. Sawakuchi; Alan C. Da Cunha; Vania Neu; Daimio C. Brito; Diani F. Da Silva Less; Joel E. M. Diniz; Aline De Matos Valerio; Milton Kampel; Alex V. Krusche; et al. (Frontiers in Marine Science, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

A phylogeny of Lophocoleaceae-Plagiochilaceae-Brevianthaceae and a revised classification of Plagiochilaceae - Simon D. F. Patzak; Matt A. M. Renner; Alfons Schäfer-Verwimp; Kathrin Feldberg; Margaret M. Heslewood; Denilson F. Peralta; Aline Matos de Souza; Harald Schneider; Jochen Heinrichs (Organisms Diversity & Evolution, 2016)

Geology of the Rosário–Neves Corvo antiform, Iberian Pyrite Belt, Portugal: new insights from physical volcanology, palynostratigraphy and isotope geochronology studies - J. T. Oliveira; C. J. P. Rosa; Z. Pereira; D. R. N. Rosa; J. X. Matos; C. M. C. Inverno; T. Andersen (Mineralium Deposita, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

sTNFR-1 is an early inflammatory marker in community versus institutionalized elderly women - Fernanda Matos Coelho; F. M. S. Narciso; D. M. G. Oliveira; D. S. Pereira; A. L. Teixeira; M. M. Teixeira; D. G. Souza; L. S. M. Pereira (Inflammation Research, 2010)

Cholesterol depletion by methyl-?-cyclodextrin enhances myoblast fusion and induces the formation of myotubes with disorganized nuclei - Cludia S. Mermelstein; Dbora M. Portilho; Rommel B. Medeiros; Aline R. Matos; Marcelo Einicker-Lamas; Giovane G. Tortelote; Adalberto Vieyra; Manoel L. Costa (Cell and Tissue Research, 2005)